Compatibіlization of polymeric composition filled with ground tire rubber – short review - Formela, Magdalena; Haponiuk, Jozef; Jasinska-Walc, Lidia; Formela, Krzysztof (Publishing House of Lviv Polytechnic National University, 2014)
Waste rubber is recognized as a valuable materials resource and searching for new recycling methods is the main activity of many research institutions and companies. During last years only few scientific papers concerning foamed polymer compositions filled with ground tire rubber were published. The paper reviews the progress in compatibilization and foaming of polymeric compositions filled with a ground tire rubber. Показано, що пошук нових методів перероблення гумових відходів, як цінної сировини, є головним видом діяльності багатьох науково-дослідних інститутів і компаній. Розглянуто компатибілізацію і спінювання полімерних композицій з наповнювачем шинна гума.
Спінювання як альтернатива компатибілізації полімерної композиції з наповнювачем шинна гума – огляд
Keywords: ground tire rubber; rubber recycling; foaming; polymer composition; compatibilization; гумова шина; гума утилізації; спінювання; полімерна композиція; компатибілізація